(untitled) (Cadernos de Psicologia Social do Trabalho, 2021)
This text was initially published as a preface written by Yves Clot in honor of Ivar Oddone. We decided to publish it as an article, authorized by the author, as we believe that it brings important and current contributions to the field of work, in interseccion with several theories: Clinic of Activity, Ergology, Ergonomics, Worker's Health, among others. In this text, Yves Clot takes up highlights of Ivar Oddone's work and produces reflections about its original aspects, not always considered by experts in the field. Thus, he makes a comparative analysis with those aspects and the proposals presented by Elton Mayo, which have become an important tool for the development of industrial capitalism under the supposed appreciation of the human sides in work situations. Contrary to Mayo's conceptions and practices, which were aimed at increasing the productivity of companies and, therefore, at the exploitation of workers, Oddone sought to recognize and value the knowledge of workers, intending that this was used as a kind of counterpower, by expanding its power to act in the work situation, points that are widely discussed by Clot in the text that we present now.